Meningkatkan Hasil Belajar PPKN Menggunakan Model PBL Berbantuan Media Smart Box Pancasila pada Siswa Kelas IV SDN 3 Kanigoro - Hasna Salsabila Khoirunnisa; Sri Hartini; Maeva Juliana Ningtyas; Melik Budiarti (Mataram University, 2026)
Learning outcomes in Pancasila and Civic Education (PPKn), particularly on the topic of Pancasila, remain unsatisfactory because many students experience difficulties in understanding concepts through conventional teacher-centered instruction. Therefore, innovative learning models supported by engaging instructional media are needed to promote active participation and improve students' understanding. This study aimed to improve students' learning outcomes in Pancasila and Civic Education (PPKn) on the topic of Pancasila through the implementation of the Problem-Based Learning (PBL) model assisted by the Smart Box Pancasila learning media for fourth-grade students at SDN 03 Kanigoro. This study employed Classroom Action Research (CAR), which was conducted in two cycles consisting of planning, action, observation, and reflection. The participants were 15 fourth-grade students. Data were collected through tests, observations, and documentation and analyzed using descriptive analysis. The findings revealed that the implementation of the Problem-Based Learning model assisted by Smart Box Pancasila effectively improved students' learning outcomes and classroom participation. The percentage of students achieving the minimum mastery criterion increased from 33% in the pre-cycle to 67% in Cycle I and reached 100% in Cycle II. In addition, students became more actively involved in discussions, expressed their opinions more confidently, collaborated effectively with peers, and demonstrated better problem-solving skills related to Pancasila. The Smart Box Pancasila media also created a more engaging, interactive, and student-centered learning environment. Therefore, the implementation of the Problem-Based Learning model assisted by Smart Box Pancasila was proven to be effective in improving the learning outcomes of fourth-grade students in Pancasila and Civic Education.